Sustainable Data Centers in Southeast Asia: Offshore, Nearshore, and Onshore Systems for Integrated Data and Power. (June 2022) - Ichinose, Yasuo; Hayashi, Michio; Nomura, Shunichiro; Moser, Bryan; Hiekata, Kazuo
Highlights: Data center and power plant designed as an integrated infrastructure system. Systemic needs of the infrastructure evaluated using a Stakeholder Value Network. Cost and CO2 simulated for various data center concepts for cities across SE Asia. Near-shore or offshore concepts are suitable for Singapore with 50% CO2 reduction. Abstract: While data centers are increasingly important for modern society owing to the expansion in data processing demand, they also contribute to emissions and thus global warming. The design of such social infrastructure requires sociotechnical evaluation, including the identification of the different needs of multiple stakeholders. This study designs and proposes concepts for data center systems as integrated infrastructure consisting of both data center and green power plant in response to rapid regional growth and potential of offshore and nearshore infrastructure in Southeast Asia. To design such an infrastructure involving multiple stakeholders with differing needs, a systems approach is employed to analyze stakeholder values and system functions leads to the identification of key stakeholders and system requirements. Subsequently, a quantitative multi-objective model based on prioritized stakeholder needs and system requirements was developed to comprehensively evaluate the data center design tradespace. Simulation results of multiple location across the region imply that Singapore is an attractive location for investment given an offshore data center with an offshore fixed wind power plant that can contribute to a 50% reduction in scaling difficulty and a 50% reduction in lifetime CO2 emissions compared to onshore data centers with solar plants, while 5% increase of total investment.